Requirements for the development of desert tourism projects in the light of SDGs objectives - Bouhafs, Rouani; Dahou, Slimane (Finance and Business Economies Review, 2019)
Algeria's dependence on oil as the sole source of foreign currency and financing for development, and the negative effects on the national economy as a result of its low prices in the world market, made the policy of economic diversification an urgent necessity, and with the tourism potential that is rich in Algeria, The sector is a key solution to attracting foreign tourists and making it a driving force for economic growth in Algeria. Despite the poor contribution of desert tourism to the economy as a result of bureaucratic obstacles and other problems, but the bodies supervising the tourism institutions to respect the specifications of eco-tourism for the sustainability of tourism development.